Dimensions and stages of the CSR maturity - Głuszek, Ewa (Research Papers of Wrocław University of Economics, 2018)
Maturity models can be treated as a guide for managers, translating knowledgeinto concrete actions to change and improve the organization. Their primary role is first of allto enable the diagnosis of the current state and to indicate the direction of activities allowingto eliminate all missing skills in a specific field. Maturity models related to corporate socialresponsibility management generally contain similar components (dimensions) and proposefive to seven stages of maturity. However, since their publication, new concepts have emerged,deepening understanding and organizing the very complex domain of CSR. The aim of thearticle is to consider the possibility of including in the CSR maturity model two dimensionsderived from newer concepts of corporate social responsibility: the type of CSR and spheresof influence. These dimensions meet the condition of disconnection and gradability, andcomplement the earlier models
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 520; s. 64-80
Keywords: maturity model; corporate social responsibility; type of CSR; sphere of influence; model dojrzałości; społeczna odpowiedzialność biznesu; typ CSR; sfera wpływu